Contribution of risk factors to the development of adverse cardiovascular events in Kemerovo Oblast population: data from a prospective study - Gaziev, T. F.; Mulerova, T. A.; Tsygankova, D. P.; Nakhratova, O. V.; Bazdyrev, E. D.; Artamonova, G. V. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2025)
Aim . To assess the rate of a combined endpoint (fatal and non-fatal cardiovascular events) and the contribution of cardiovascular risk factors to its development in Kemerovo Oblast population. Material and methods . A clinical and epidemiological prospective study was conducted in the Kemerovo Oblast at the Research Institute for Complex Issues of Cardiovascular Diseases. The first stage (20172019) was inclusion of respondents and examination (n=1600). Prospective stage (2020-2021) included re-examination after 3 years sical inactivity, and smoking. The composite endpoint (CEP) included fatal and non-fatal cardiovascular events. Results . Individuals with CEP were characterized by higher cardiome obesity (OR=2,12, p=0,001), abdominal obesity (OR=2,65, p=0,001) and carbohydrate metabolism disorders (OR=1,88, p=0,001) were associated with the risk of CEP. Taking into account the significance criterion (Wald), the CEP probability over a 3-year period was determined by the following variables: age (Wald test 32,8), abdominal obesity (Wald criterion 19,3), hypercholesterolemia (Wald criterion 8,8) and obesity (Wald criterion 7,3). Conclusion . The study results emphasized the role of regional factors in the risk of adverse cardiovascular events, justifying the need for similar studies in other Russian regions.